Predicting High-Grade Acute Urinary Toxicity and Lower Gastrointestinal Toxicity After Postoperative Volumetric Modulated Arc Therapy for Cervical and Endometrial Cancer Using a Normal Tissue Complication Probability Model - Tianyu Yang; Zhe Ji; Runhong Lei; Ang Qu; Weijuan Jiang; Xiuwen Deng; Ping Jiang (Current Oncology)
(1) Background: Volumetric modulated arc therapy (VMAT) can deliver more accurate dose distribution and reduce radiotherapy-induced toxicities for postoperative cervical and endometrial cancer. This study aims to retrospectively analyze the relationship between dosimetric parameters of organs at risk (OARs) and acute toxicities and provide suggestions for the dose constraints. (2) Methods: A total of 164 postoperative cervical and endometrial cancer patients were retrospectively analyzed, and the endpoints were grade ≥ 2 acute urinary toxicity (AUT) and acute lower gastrointestinal toxicity (ALGIT). The normal tissue complication probability (NTCP) model was established using the logistic regression model. Restricted cubic spline (RCS) curves were used to explore the association between dosimetric parameters and toxicities. The receiver operating characteristic (ROC) curve, calibration curve, Akaike’s corrected information criterion (AICc), decision curve analysis (DCA), and clinical impact curve (CIC) were analyzed to evaluate the performance of NTCP models. (3) Results: Bladder V40Gy was identified to develop the NTCP model of AUT, and the mean AUC was 0.69 (CI: 0.58–0.80). Three candidate predictors, namely the small intestine V30Gy, colon D45%, and rectum D55%, were identified to develop the NTCP model of ALGIT, and the mean AUC was 0.71 (CI: 0.61–0.80). Both models were considered to have relatively good discriminative accuracy and could provide a high net benefit in clinical applications. (4) Conclusions: We developed NTCP models to predict the probability for grade ≥ 2 AUT and ALGIT. We recommend that bladder V40Gy, the small intestine V30Gy, colon D45%, and rectum D55% be controlled below 42%, 20.4%, 16.9 Gy, and 32.0 Gy, respectively.